À mourir de peur/rire : The Great God Pan d’Arthur Machen (1894) - Sophie Mantrant (Cahiers Victoriens et Edouardiens)
The Great God Pan, Machen’s first major success, is a dark tale that exploits late Victorian anxieties about scientific progress, especially the post-Darwinian fear/fantasy of regression to bestial levels. The text seems intent on making the reader’s flesh creep, and yet many early reviewers stated that it failed to do so, some going as far as claiming that the novella made one shake with laughter rather than with dread. The aim of this article is to highlight the semantic, structural and stylistic ingredients used to arouse dread or anxiety and, ultimately, to try and determine why Machen’s text has failed to generate the « appropriate » emotional response.